Validation of the technology acceptance for electronic dinar payment system - Mohd Nazri Muhayiddin; Elsadiq M.A.; Hishamuddin Ismail (2012)
This study is intended to solve a few constraints existed in physical gold dinar when used as a form of payment. One dinar is equal to 4.25 gram of fine gold. Specifically, this work proposes the use of e-commerce technology to solve those constraints. But before the actual system can be implemented, this research seeks to find out whether or not the public would be ready to adopt the concept of an electronic dinar payment system. The research framework is based on Unified Theory of Acceptance and Use of Technology (UTAUT) (Venkatesh et al., 2003). It measures the user acceptance based on these constructs; performance expectancy, effort expectancy, social influence, facilitating conditions, behavioral intention to use. In addition, attitude toward using, anxiety and perceived credibility are added as three new constructs. Data collection is based on a questionnaire survey, which was distributed to 1000 respondents throughout Malaysia (Peninsula). The response rate was 87.2% (872 respondents had answered it completely). This paper discusses the the validation of measurement model for electronic dinar payment system using SPSS v17.0 and AMOS v18.0 analytical tools. Based on the analysis of measurement model, it is found that there are a total of 25 factors that may have influenced the intention to use electronic dinar payment system. These 25 factors load successfully into the seven (7) main constructs with acceptable goodness-of-fit indices (GOF > 0.90). The results would be useful for the Malaysian Government, local banks, institutions which offer electronic payment services, wholesalers, retailers, and most importantly for the ordinary consumers